Hardware and Software Complex to Determine the Strength Parameters of Composite Materials and Structural Elements of Rocket and Space Equipment - Drozdov, O.V. (Science and Innovation, 2024)
A hardware and software complex has been developed to determine the strength parameters of promising carbon fiber reinforced polymers and structural elements of rocket and space equipment under different mechanical loads within the operating temperature range. The developed complex components, in particular, the multi-channel data-measuring systems and the appropriate software for measurement, acquisition of experimental data, and calculation of strength parameters of such materials have been described. The complex capacity and effectiveness have been tested.